Identification of an ancestral haplotype of the 35delG mutation in the GJB2 (connexin 26) gene responsible for autosomal recessive non-syndromic hearing loss in families from the Eastern Black Sea Region in Turkey - Balci, Burcu; Gerçeker, Filiz Ozbaş; Aksoy, Songül; Sennaroğlu, Gonca; Kalay, Ersan; Sennaroğlu, Levent; Dinçer, Pervin (The Turkish Journal of Pediatrics, 2005)
Mutations in the GJB2 gene have been shown to be the major cause of autosomal recessively inherited, prelingual, non-syndromic hearing loss. 35delG was found to be the most frequent mutation among Caucasians. In this study, we performed haplotype analysis of two large families with autosomal recessive non-syndromic hearing loss (totally 33 affected, 37 unaffected) from Trabzon (a city from the Eastern Black Sea region) by using polymorphic markers close to the 35delG mutation region, and identified a common haplotype, "2-6-4". The frequency of the mutant chromosomes having the 2-6-4 haplotype was compared between the Eastern Black Sea region and the other regions of Turkey and the difference was found to be significant (chi squared = 5.13/df = 1/p = 0.023). Also, when the frequency of mutant and wild type chromosomes having the 2-6-4 haplotype was compared in the Eastern Black Sea region, a statistically significant difference was observed in the mutant chromosomes (chi squared = 7.46/df = 1/p < or = 0.01). The results of this study demonstrate that the ancestral haplotype of the chromosomes bearing 35delG mutation in the Eastern Black Sea region is "2-6-4".